Acremonium keratitis in a patient with healed herpetic eye disease - Rashmeet Arora (Journal of Clinical Ophthalmology and Research, 2020)
We report the case of a 65-year-old male who presented with pain, diminution of vision, redness foreign-body sensation, and watering for 1 month. The patient was a known case of bronchial asthma and was on inhalational budesonide treatment for 3 years. The patient had cataract surgery 18 months back and has a history of herpetic eye disease. Corneal cultures were positive for acremonium.